HUBUNGAN TINGKAT PENDIDIKAN TERHADAP PENGETAHUAN PENGGUNAAN ANALGETIK PADA MASYARAKAT DUSUN BANYUMENENG 2 GIRIHARJO PANGGANG GUNUNGKIDUL PERIODE JANUARI 2022 - Dian Nur Afriyani; Dwi Hastuti (Universitas Haji Sumatera Utara, 2022)
Based on the 2018 riskasdes, the prevalence of pain in Yogyakarta was 7,3%. Analgesic is one of the drugs that are often used for treatment with a percentage of 36,2-59%. Analgesic drugs can relieve pain such as menstrual pain, toothache, and headaches. Inappropriate use of analgesics in the community can cause adverse side in the long term. Sereval studies show that public knowedge is still lacking in the use of analgesics. The purpose of this study was to determine the relationship between aducation level and knowledge of analgesic use in community of Banyumeneng 2, Giriharjo, Panggang, Gunungkidul Period January 2022. The research method used is analytic observasional with a cross sectional approach. Data collection using purposive sampling technique using a knowledge questionnaire, the result abtained are processed and analyzed using SPSS 23 with Chi Square test. The number of subjects in the study were 88 respondents. This study shows that the result of the Chi-Square test obtained the Asymp value. Sig 0,000 is less than 0,05 which means Ha is accepted so it can be concluded that there is a relationship between education level and knowledge of analgesic use. The conclusion of this study is that there is a relationship between the level of education and knowledge of the use of analgesics.